PEMBERDAYAAN IMAN KELUARGA KATOLIK MELALUI KEGIATAN LINGKUNGAN DI STASI SUMBER BENING DAN WIDODAREN PAROKI ST. YOSEF NGAWI - Wilhelmus, Ola Rongan (Bahasa Indonesia, 2024)
Many Catholic couples and families today prefer to choose the easy and shortcut way to solve the problems and challenges related to the family and marriage life. For example, problems of infidelity, economics, domestic violence are often resolved by divorce. This settlement proved to have many negative impacts on the family life. Recognizing these various family challenges and problems, the Surabaya Diocese's pastoral activities during 2023 focussing on the pastoral theme: Living Christ in the Family". During this period, families were guided through various Basic Christian Community's pastoral activities to explore the said pastoral theme. Those activities were part of empowering the faith of Catholic families. The research was conducted with the aim to identify the perception of Catholics at Sumber Bening and Widodaren Basic Christian Communities at Saint Yosef Parish, about the meaning of the Catholic family, discipleship in the family, and empowerment of the Catholic family's faith. The research used a quantitative approach, and the research model used was a survey. The research respondents were heads of Catholic families in the said two Basic Christian Communities. Data collection was carried out using questionnaire techniques, and the data was analyzed descriptively-statistically. The results of the study revealed that majority of respondents said that family is a community and living relationships between individuals who are imbued with the spirit of wholeness, love and gentleness. Families need to have a mature faith in Jesus Christ, and this mature faith requires better and more varied faith empowerment programs and strategies.